Self-Leveling Laser for Direction Marking System - Hazliza Ariffin, Nur; Arsad, Norhana; Hariz Ahmad, Azri; Bais, Badariah; Kamal, Noorfazila; Ab Aziz, Norazreen; Salasiah Mokri, Siti; Mohd Mydin, Raihanah (International Journal of Engineering and Technology, 2019)
The laser has the ability to radiate a fine shaft of light within a certain distance, yet it will produce excess infrared light that is invisible to the eye. Direct exposure towards the infrared light is extremely dangerous as it can cause serious eye damage. Therefore a self-leveling laser for direction marking system is proposed to control the movement of the laser and to reduce the risk of direct exposure to the eye. The development of the system is achieved with a Micro-Electro-Mechanical System (MEMS) gyroscope and accelerometer to support the structure orientation of the mounted laser on a servo motor before the laser emits light. Data from both sensors are successfully merged through a complementary filter with a filter factor, a = 0.97. Moreover, the light intensity of 532 nm green and 650 nm red wavelength laser diodes were measured using a spectrometer and the comparison shows that the green laser has a narrower linewidth as the distance is increased.Â Â Â